Significados da solidariedade na bodega nordeste vivo e solidário, no Ceará - Pereira, Janainna Edwiges de Oliveira (2017)
The present work has as its theme the Solidary Economy and the Bodega Nordeste Vivo e Solidário as an empirical experiment to be analyzed, a solidarity productive enterprise that is part of the Rede Bodega, a solidary economy network of the state of Ceará, which brings artisans and craftsmen, farmers from five groups located in different municipalities. I intend to interpret the meanings attributed by three women of such an undertaking to the notion of solidarity and to the relations existing between the groups that integrate it, as well as their practical experiences in this solidarity enterprise. For this, I chose as an empirical focus two groups of Prainha do Canto Verde that integrate the unit based in the municipality of Aracati, Bodega Nordeste Vivo e Solidário, which is formed by 54 groups that work with family agriculture, handicrafts, food services and lodging. In videos published by the Rede Bodega, as well as in its institutional discourse, solidarity is emphasized as a fundamental point for strengthening groups and for the realization of an economy based on principles of solidarity, as opposed to a market economy, aimed at profit and Is largely based on social relations of exploitation. In this way, I will try to understand the representations of some of its members about the elements and symbols that unite them so that they work and identify themselves as members of the same project, the Rede Bodega, which has as one of its main pillars solidarity. Methodologically, I opt for an ethnographic approach in which I conduct a research with qualitative data collection procedures, with emphasis on field research, observation and open interviews, with a priority focus on understanding the life narratives of three members of Bodega Nordeste Vivo e Solidário.